2022
DOI: 10.1037/bar0000237
|View full text |Cite
|
Sign up to set email alerts
|

Give the dog a big bone: Magnitude but not delivery method of food impacts preference and reinforcer efficacy in dogs.

Abstract: Despite the prevalence of reinforcement-based training practices in animal training, little research has investigated how to enhance the efficacy of delivered consequences; effective reinforcers are critical for maintaining long chains of behavior, such as in working animals, and for competing with environmental reinforcers. Two potentially easy methods to increase efficacy of reinforcers used in animal training are increasing magnitude (e.g., deliver 4 pieces of food instead of 1) or altering delivery (e.g., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…That we found no differences in responding between 4-s and 30-s social interactions was not expected given that the magnitude of reinforcement often affects reinforcer value (e.g., Hoch et al, 2002;Hodos & Kalman, 1963;Nader & Woolverton, 1991), including in dogs (Feuerbacher et al, 2022). However, there might be differences that we did not detect; in an effort to reduce satiation as a possible factor, we capped sessions at 10 trials.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…That we found no differences in responding between 4-s and 30-s social interactions was not expected given that the magnitude of reinforcement often affects reinforcer value (e.g., Hoch et al, 2002;Hodos & Kalman, 1963;Nader & Woolverton, 1991), including in dogs (Feuerbacher et al, 2022). However, there might be differences that we did not detect; in an effort to reduce satiation as a possible factor, we capped sessions at 10 trials.…”
Section: Discussionmentioning
confidence: 66%
“…Prior research has suggested that petting, but not vocal praise, can function independently as a reinforcer for dog behavior (McIntire & Colley, 1967). More recent research has found vocal praise is not a preferred reinforcer for dogs (Feuerbacher & Wynne, 2015) and does not influence the reinforcer value of food when delivered simultaneously with food (Feuerbacher et al, 2022). Additionally, investigating different forms of petting and its possible interaction with response topography would be useful; we used more active massaging and scratching petting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As with training, the target response was a muzzle touch to the target, though during testing the horse had to walk back and forth across the testing stall to access the target. Horses worked on a Basis 2 Progressive Ratio 1 schedule (Feuerbacher et al, 2022 ; Vicars et al, 2014 ), such that the horse had to complete each response requirement twice before the response requirement was increased by one touch. Response requirements began at one touch at the beginning of each testing session.…”
Section: Methodsmentioning
confidence: 99%